Model of human occupation : theory and application - Kielhofner, Gary, 1949-2010 (Baltimore (Md.) : Lippincott Williams & Wilkins, 2008)
The only complete and current presentation of the most widely used conceptual practice model in occupational therapy. This revised edition goes beyond earlier editions in examining how theory comes to life in practice. Included are numerous assessments, case examples, photographs, and other resources that were developed by therapists throughout the world who have identified new ways to expand and apply this model to practice.
Includes bibliographical references (p. 532-549) and index.
Keywords: Models, Psychological; Occupational Therapy; Occupational therapy